The Concept of Insān kāmil in the Perspective of Contemporary Sufism - Redi Irawan; Abol Fazl Tajik; Adel Meghdadiyan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article discusses how the concept of Insan Kamil is perceived in contemporary Sufism. The fundamental principle of Sufism is Tawhid, and if Tawhid is lost from a believer, the essence of the human heart will change, causing them to fall from the dignity of humanity. In other words, the concept of wahdat al-wujūd is a direct consequence of Tawhid, which subsequently gives rise to the concept of insān kāmil. To analyze this discussion, the author employs an analytical-descriptive method, ultimately concluding that in the thoughts of contemporary Sufis, both from Persia, such as Ayatollah Imam Khomeini and Ayatollah Hasan Zadeh Amuli, as well as contemporary Sufis in Indonesia like Abah Guru Sekumpul and Emha Ainun Nadjib, there is a commonality regarding the Divine Essence of Allah Swt, which is beyond the understanding of past or future, transcends time and space, and has no representation of the Divine Essence. Insan Kamil is viewed as the locus of the manifestation of all the most perfect names of Allah Swt. According to them, all the characteristics of Insan Kamil are manifested in the person of the Prophet Muhammad Pbuh. Therefore, anyone wishing to achieve a spiritual station of Insan Kamil should emulate the Messenger of Allah in all dimensions of his life.